Analysis of Self-Adhesive Resin Cement Microshear Bond Strength on Leucite-Reinforced Glass-Ceramic with/without Pure Silane Primer or Universal Adhesive Surface Treatment. (18th October 2015) - Lee, Yoon; Kim, Jae-Hoon; Woo, Jung-Soo; Yi, Young-Ah; Hwang, Ji-Yun; Seo, Deog-Gyu
Abstract : Objective . To evaluate the microshear bond strength ( μ SBS) of self-adhesive resin (SA) cement on leucite-reinforced glass-ceramic using silane or universal adhesive. Materials and Methods . Ceramic blocks were etched with 9.5% hydrofluoric acid and divided into three groups (n = 16 ): (1) negative control (NC) without treatment; (2) Single Bond Universal (SBU); (3) RelyX Ceramic Primer as positive control (PC). RelyX Unicem resin cement was light-cured, and μ SBS was evaluated with/without thermocycling. The μ SBS was analyzed using one-way analysis of variance. The fractured surfaces were examined using stereomicroscopy and scanning electron microscopy (SEM). Results . Without thermocycling, μ SBS was highest for PC (30.50 MPa ± 3.40), followed by SBU (27.33 MPa ± 2.81) and NC (20.18 MPa ± 2.01) (P < 0.05 ). Thermocycling significantly reduced μ SBS in SBU (22.49 MPa ± 4.11) (P < 0.05 ), but not in NC (20.68 MPa ± 4.60) and PC (28.77 MPa ± 3.52) (P > 0.05 ). PC and NC predominantly fractured by cohesive failure within the ceramic and mixed failure, respectively. Conclusion . SBU treatment improves μ SBS between SA cement and glass ceramics, but to a lower value than PC, and the improvement is eradicated by thermocycling. NC exhibited the lowest μ SBS, which remained unchanged after thermocycling.